A Right Atrial Mass with Fever and Cutaneous Nodules - Feng Gao; Stephanie Koh; Sara Taveras-Alam; Umair Khalid (Methodist DeBakey Cardiovascular Journal)
Primary cardiac tumors, although exceedingly rare, should be considered in the differential diagnosis during workup of any cardiac mass. Extranodal cardiac lymphomas have a natural aggressive course due to delayed diagnosis. We present a 71-year-old male with a dual-chamber pacemaker who presented with fevers and new cutaneous nodules. He was found to have a right atrial primary anaplastic large-cell lymphoma and had a complete metabolic response after chemotherapy. Our case highlights the importance of a multimodality approach in the diagnosis of cardiac tumors and during follow-up after treatment.